PENGARUH KUALITAS INFORMASI DAN PELAYANAN TERHADAP KEPUASAN PELANGGAN DAN MINAT BELI ULANG PADA SITUS BELANJA ONLINE SHOPEE - Malian, Marina (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2023)
The observe aims to have a look at The effect Of information pleasant And carrier excellent On client delight And Repurchase aim On on-line store websites In Shopee for patron Shopee in Indonesia. The sampling approach used in this look at is nonprobability sampling, specifically the purposive sampling technique. The range of sampling used in this observe consisted of a 170 respondents aged 18-26. The approach of amassing statistics the use of survey technique. The analytical tool utilized in the SEM (structural equation version) with the AMOS 22 application program. The result shows that information quality has a effective and enormous impact on Repurchase purpose. Carrier first-class has a fine and good sized impact on Repurchase purpose. Purchaser satisfaction has a fantastic and substantial impact on Repurchase aim. Information best has a positive and significant impact on patron pride. Service first-rate has a effective and enormous effect on client pleasure. Client satisfaction mediates statistics first-class with Repurchase aim. Client satisfaction mediates carrier nice with Repurchase intention.